Wacana Paulus di Atena (Kis 17:22-31) sebagai Tawaran Model Pertobatan Resiprokal bagi Gereja dan Budaya Setempat - Viktorahadi, R.F. Bhanu (Jurnal Orientasi Baru, 2011)
Church in Indonesia is still regarded a foreign entity in the midst of the largersociety where it stands. It comes to happen because the church is often consideredof not willing to open herself to create a dialogue with the society. In this case,Paul’s experience in Athen (Acts 17:22-31) could perhaps become inspiration for theChurch in building a sincere dialogue with her circumstance. In his conversationwith the Athenians, Paul succesfully made use of the elements which actuallybelong to the background of his partners as a means for proclaiming Jesus Christ.By doing this, at the same time, he placed the Athenians as his equal partners ofdialogue. Creating a dialogue with others is indeed a long unending process thatreally requires repentances from those who are involved in it.